От редактора - Bukh, Vladimir (проект байкал, 2007)
In the design market a personal architectural firm is identified by creative image of its head and does not offer «a pig in a poke» to the client who is concerned about high-quality architecture. Another matter is faceless ex-design institutions, which are functioning now in the form of joint-stock companies. Their design business is not determined by architecture. Their products are in demand among developers that continue to believe that architectural goals depend on the manner of their construction realization, among the developers that let builders push themselves around. But the demand for genuine architecture is awakening and strengthening. We make an attempt to show you, by the example of Irkutskgrazhdanproject, how the system of design institutions works in the new economic conditions.